Diagnosis and management of unilateral subclavian steal syndrome with bilateral carotid artery stenosis. (August 2021) - Song, David; Ireifej, Branden; Seen, Tasur; Almas, Talal; Sattar, Yasar; Chadi Alraies, M.
Abstract: Subclavian steal syndrome is a rare phenomenon occurring from retrograde blood flow in the vertebral artery due to proximal stenosis in the subclavian artery. As a result, the arm gets blood supply from the vertebral artery at the expense of the vertebrobasilar system. The patient remains largely asymptomatic until there is an increase demand for blood supply to the arm, resulting in a constellation of symptoms including dizziness, vertigo, blurred vision, diplopia, headache, syncope, postural hypotension, neurologic deficits, and rarely, memory problems. The management approach depends on the severity of clinical symptoms but includes medical treatment, endovascular therapy and lifestyle modifications. Highlights: Subclavian steal syndrome with concurrent carotid artery stenosis is only the second documented case, which makes it an extremely rare presentation or frequently unnoticed condition. Absence of symptoms does not rule out subclavian steal syndrome with bilateral carotid stenosis and should be considered in the differential in patients with high risk comorbidities with appropriate imaging and physical exam. The treatment depends on the severity of clinical symptoms but includes medical treatment, endovascular therapy and lifestyle modifications.